2002
DOI: 10.1029/2002jd002090
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Oscillation response to the 1991 Mount Pinatubo eruption: Effects of volcanic aerosols and ozone depletion

Abstract: [1] Observations show that strong equatorial volcanic eruptions have been followed by a pronounced positive phase of the Arctic Oscillation (AO) for one or two Northern Hemisphere winters. It has been previously assumed that this effect is forced by strengthening of the equator-to-pole temperature gradient in the lower stratosphere, caused by aerosol radiative heating in the tropics. To understand atmospheric processes that cause the AO response, we studied the impact of the 1991 Mount Pinatubo eruption, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
322
6
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 255 publications
(361 citation statements)
references
References 102 publications
32
322
6
1
Order By: Relevance
“…To compare the amounts of sulfate aerosols used in our geoengineering simulations to a major volcanic eruption, it may be noted that the 1991 Pinatubo eruption injected about 20 Mt of SO 2 (30 Mt of SO 4 ; Stenchikov et al 2002) into the stratosphere. Further, it should be noted that we do not inject aerosols in our simulations.…”
Section: Methodsmentioning
confidence: 99%
“…To compare the amounts of sulfate aerosols used in our geoengineering simulations to a major volcanic eruption, it may be noted that the 1991 Pinatubo eruption injected about 20 Mt of SO 2 (30 Mt of SO 4 ; Stenchikov et al 2002) into the stratosphere. Further, it should be noted that we do not inject aerosols in our simulations.…”
Section: Methodsmentioning
confidence: 99%
“…Observations and modeling studies [Hansen et al, 1992;Mao, 1992, 1995;Solomon et al, 1996;Mao and Robock, 1998;Stenchikov et al, 1998;Solomon, 1999;Stenchikov et al, 2002;Briffa et al, 2004] have shown that large tropical volcanic eruptions such as these two recent events produced general cooling effect especially in NH summers, whereas dynamically induced warming over NH continents for the next couple winters following the eruptions. The cooling is the direct result of the 4 stratospheric volcanic aerosols scattering some solar radiation back to space.…”
Section: The Climatic Impact Of Volcanismmentioning
confidence: 99%
“…There have been many studies on the effect of volcanic eruptions on global climate change (Robock 2000;Stenchikov et al 1998Stenchikov et al , 2002Stenchikov et al , 2004Stenchikov et al , 2009Kirchner et al 1999;Yang and Schlesinger 2002;Shindell et al 2004;Gleckler et al 2006;Frölicher et al 2011;Mignot et al 2011;Ottera et al 2010;Zanchettin et al 2012). The studies showed that large volcanic eruptions emit sulphur gases into the stratosphere, which become sulphate aerosols.…”
Section: Introductionmentioning
confidence: 99%